The Relationship Between Viral Load Levels and the Incidence of Oral Candidiasis in HIV/AIDS Patients at Jombang Hospital for the Period 2023-2025 - Elffanna Listrianingtias; I Dewa Made Widi Hersana; Dian Ardiana (Green Publisher Indonesia, 2026)
This research aimed to determine the relationship between viral load levels and the incidence of oral candidiasis among HIV/AIDS patients at the RSUD Jombang during the 2023–2025 period. This analytical observational study with a cross-sectional design used secondary data from medical records of HIV/AIDS patients at RSUD Jombang (2023–2025). The independent variable was viral load level and the dependent variable was oral candidiasis incidence. Data were analyzed using univariate and bivariate analyses (Kruskal-Wallis and Chi-Square tests), examining viral load and other variables including age, gender, occupation, comorbidity, marital status, education level, and antifungal medication use. The research involved 402 patients, of whom 322 (80.1%) had an undetectable viral load, 26 (6.5%) had a suppressed viral load, and 54 (13.4%) had an unsuppressed/high viral load. Bivariate analysis showed that neither numerical viral load (p=0.97) nor ordinal viral load (p=0.22) had a significant relationship with the incidence of oral candidiasis. Other variables such as age (p=0.18), gender (p=0.88), occupation (p=0.62), comorbidity (p=0.71), marital status (p=0.08), and antifungal medication use (p=0.64) also showed no significant relationship. However, educational level was found to have a significant association with the incidence of oral candidiasis (p=0.04). Overall, these findings suggest that educational level plays an important role in the occurrence of oral candidiasis among HIV/AIDS patients, indicating that targeted educational interventions and increased patient awareness regarding viral load management and oral hygiene may help reduce the incidence of this infection.